Plant Evolution History Overwhelms Current Environment Gradients in Affecting Leaf Chlorophyll Across the Tibetan Plateau - He, Yicheng; Li, Tingting; Zhang, Ruiyang; Wang, Jinsong; Zhu, Juntao; Li, Yang; Chen, Xinli; Pan, Junxiao; Shen, Ying; Wang, Furong; Li, Jingwen; Tian, Dashuan (Frontiers in Plant Science, 2022)
Aims Leaf chlorophyll (Chl) is a fundamental component and good proxy for plant photosynthesis. However, we know little about the large-scale patterns of leaf Chl and the relative roles of current environment changes vs. plant evolution in driving leaf Chl variations. Locations The east to west grassland transect of the Tibetan Plateau. Methods We performed a grassland transect over 1,600 km across the Tibetan Plateau, measuring leaf Chl among 677 site-species. Results Leaf Chl showed a significantly spatial pattern across the grasslands in the Tibetan Plateau, decreasing with latitude but increasing with longitude. Along with environmental gradient, leaf Chl decreased with photosynthetically active radiation (PAR), but increased with water availability and soil nitrogen availability. Furthermore, leaf Chl also showed significant differences among functional groups (C4 > C3 species; legumes < non-legume species), but no difference between annual and perennial species. However, we surprisingly found that plant evolution played a dominant role in shaping leaf Chl variations when comparing the sum and individual effects of all the environmental factors above. Moreover, we revealed that leaf Chl non-linearly decreased with plant evolutionary divergence time. This well-matches the non-linearly increasing trend in PAR or decreasing trend in temperature during the geological time-scale uplift of the Tibetan Plateau. Main Conclusion This study highlights the dominant role of plant evolution in determining leaf Chl variations across the Tibetan Plateau. Given the fundamental role of Chl for photosynthesis, these results provide new insights into reconsidering photosynthesis capacity in alpine plants and the carbon cycle in an evolutionary view.